Replacement heifers-Health program - T.B. Avery (Kansas Agricultural Experiment Station Research Reports, 1986)
Common disease causing agents are identified and a sample replacement heifer health program is presented. Written objectives are useful for evaluation of heifer rearing.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Replacement heifers; Colostrum; Immunoglobin